ASTRONOMICAL OBSERVATORY AT KOLONICKE SEDLO AND ITS RESULTS IN VARIABLE STARS OBSERVING - Kudzej, I.; Karetnikov, V. G.; Dubovsky, P. A.; Paulin, L. S.; Fashchevskyi, N. N.; Ryabov, A. V.; Dorokhova, T. N.; Dorokhov, N. I.; Koshkin, N. I.; Vadila, M.; Parimucha, S. (Одеські астрономічні публікації, 2007)
There is presented a brief report of the actual equipments in the Astronomical Observa tory at the Kolonicke Sedlo. Description of Vihorlat National Telescope of 1 meter diameter equipped with the two-star high-speed photoelectric photometer and autoguiding system as well as various small telescopes capabilities are included. The results of CCD and PMT observations are presented. The future observational programs are presented as well.